THE VALIDITY AND RELIABILITY OF FIVE-TIER CONCEPTION DIAGNOSTIC TEST FOR KINETIC THEORY OF GASES - SAADATUL FAJRIYYAH, NORIYATUS; ULFAH ERMAWATI, FRIDA (Inovasi Pendidikan Fisika, 2020)
Misconceptions was reported to occur in many concepts in Physics subject in senior high school. One of them is in Kinetic Theory of Gases concepts. For example, students assumed if two balloons with different volumes are connected using a plastic straw, the air will flow from the bigger balloon to the small balloon. This assumption is not in accordance with the Kinetic Theory of Gases concept namely Boyle?s Law, so it is called misconception. The aims of this study is to develop a five-tier conception diagnostic test for Kinetic Theory of Gases and determine the validity and the reliability. The author using two different samples, first, 27 students to collect reasons, second, 35 students to gain validity and reliability score. The validity aspect consists of internal and external validities. The internal validity has done by two Physics lecturers. The external validity consists of content and construct aspect. The external validity of the content was determined based on false positives (FP) and false negatives (FN) values that < 10%, while the construct external validity was determined using the Pearson Product Moment correlation equation. The reliability was calculated using Alfa Cronbach (r_11) with 5% significance level and rtheoritic of 0.334. The internal validity results is 94.33%. The FP and FN values are 8.9 and 7.8% respectively, which means that the developed instrument is valid. The (r_xy) is 0.64, while the reliability value (r_11) is 0.885. Those values are greater than the rtheoritic, which means that the developed instrument is valid and reliable.Keywords: Kinetic theory of gases, five-tier conception diagnostic test, validity, reliability